Identificação dos principais atributos para o projeto de uma rede cicloviária - Pitilin, Taiany Richard (Universidade Federal de São Carlos, 2016)
The aim of this research project was to identify what the key attributes that should be considered in the design of a cycling network from the point of view of cyclists and transport planning experts. The methodology for development of research consisted of: (1) application of questionnaires to cyclists on the factors that influence the choice of your routes, (2) application of questionnaires to experts about what attributes should be considered in planning a cycling route urban area and (3) Analysis of the results using statistical methods. The survey results were analyzed using the method of successive intervals, also applying t test and ANOVA for comparison of results. From the results of these two studies was possible to identify the aspects considered important for cyclists and experts, analyzing their divergences and proposing guidelines for project cycling networks that meet the needs of cyclists and attract new users.
Keywords: Escolha das rotas de ciclistas; Definição de rota ciclável; Rede cicloviária; Choice of routes cyclists; Definition of cycling route; Cycling network; ENGENHARIAS::ENGENHARIA CIVIL